Art and dis-illusion in the long sixteenth century - Silver, Larry (Brill's studies on art, art history, and intellectual history, 2023)
"While entire libraries discuss the religious and political history of the sixteenth century in Northern Europe, focused on the Reformation and the rise of nation-states, Larry Silver uniquely traces the dramatic, even traumatic changes of the Reformation era through visual culture, paintings as well as the new medium of prints. Among featured shifts are the destruction of church images, witchcraft, reactions to new voyages of exploration, and issues of vision itself in an age of increasing re-examination of morality as well as sin and death"--